2009
DOI: 10.3324/haematol.2008.003632
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risk of chronic lymphocytic leukemia and other indolent non-Hodgkin's lymphomas among relatives of patients with chronic lymphocytic leukemia

Abstract: BackgroundPrevious studies have shown increased familial risk for chronic lymphocytic leukemia. In the most comprehensive study to date, we evaluated risk of chronic lymphocytic leukemia and lymphoproliferative disorders among first-degree relatives of chronic lymphocytic leukemia cases compared to first-degree relatives of controls. Design and MethodsPopulation-based registry data from Sweden were used to evaluate outcomes in 26,947 first-degree relatives of 9,717 chronic lymphocytic leukemia patients (diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 32 publications
(40 reference statements)
5
83
0
2
Order By: Relevance
“…For prostate cancer, the best-fitting estimate of the genetic correlation between aggressive and nonaggressive disease was at the upper boundary (ρ = 1, SE = 0.25), indicating a * Comparison of first-degree familial relative risk (95% CI) measured by our genome-wide association study (last column) with estimates of familial relative risk from the three largest family studies. Prior estimates are from (1,6,10), except for CLL (31), DLBCL (32), glioma (sibling) (33), pancreas (34), and esophagus (3). CI = confidence interval; CLL = chronic lymphocytic leukemia; DLBCL = diffuse large B-cell lymphoma; ER = estrogen receptor; FRR = family relative risk; GWAS = genome-wide association study.…”
Section: Articlementioning
confidence: 99%
“…For prostate cancer, the best-fitting estimate of the genetic correlation between aggressive and nonaggressive disease was at the upper boundary (ρ = 1, SE = 0.25), indicating a * Comparison of first-degree familial relative risk (95% CI) measured by our genome-wide association study (last column) with estimates of familial relative risk from the three largest family studies. Prior estimates are from (1,6,10), except for CLL (31), DLBCL (32), glioma (sibling) (33), pancreas (34), and esophagus (3). CI = confidence interval; CLL = chronic lymphocytic leukemia; DLBCL = diffuse large B-cell lymphoma; ER = estrogen receptor; FRR = family relative risk; GWAS = genome-wide association study.…”
Section: Articlementioning
confidence: 99%
“…3 Furthermore, we found significantly increased risk for NHL, including LPL/WM, and hairy cell leukemia. 15 However, there was no excess of HL, MM or MGUS (Table 1). These studies support the role of germ-line genes underlying risk of CLL and perhaps related malignancies.…”
Section: Lymphomasmentioning
confidence: 99%
“…11 We have evaluated the familial risk of CLL in two studies. 15,19 Recently, a study including almost 10,000 CLL patients and their close to 27,000 first-degree relatives showed that first degree relatives of CLL patients had an 8.5-fold increased risk for CLL. 15 This is similar to that observed in a registry study in Utah.…”
Section: Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This study was based on an analysis of 9,717 CLL cases and 38,159 controls ascertained through the Swedish Cancer Registry. Findings underscored CLL being characterized by a high familial relative risk (RR) -the RR of CLL in first-degree relatives of cases in this study was seen to be increased 8.5-fold.…”
Section: Familial Risks Of Chronic Lymphocytic Leukemiamentioning
confidence: 99%